2019
DOI: 10.14742/ajet.5552
|View full text |Cite
|
Sign up to set email alerts
|

Identity and digital equity: Reflections on a university educational technology course

Abstract: This inquiry explored preservice teachers (PSTs) developing learner and professional identities while participating in a university course that explicitly incorporates the use of technology into teaching. The paper posits that it is important for initial teacher education to explicitly engage with the role of technology in these developing identities to minimise the risk of digital inequity, both for PSTs’ learning and that of their future students. Two central questions are addressed: How did PSTs make sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…The Risk of Digital Inequity (4.55%). McLay and Reyes (2019) explored identity and digital equity by conducting an exploratory case study to learn about participants’ reflections on the role of technology in developing identity. McLay and Reyes reported that failing to address the feeling of discomfort with technology (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The Risk of Digital Inequity (4.55%). McLay and Reyes (2019) explored identity and digital equity by conducting an exploratory case study to learn about participants’ reflections on the role of technology in developing identity. McLay and Reyes reported that failing to address the feeling of discomfort with technology (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…McLay and Reyes (2019) argued that preservice teachers’ attitudes toward the role of technology influence their developing identity. For example, if they lack autonomy or feel overwhelmed by educational technology, they experience digital inequity, which impacts their professional identity.…”
Section: Resultsmentioning
confidence: 99%
“…By forming communities of practice, preservice teachers can exchange their educational experiences and keep abreast of the most recent research findings and develop a collaborative identity (Cho, 2016). As regards the challenges of TALL, negative self‐image (Vella, 2013) for those teachers who suffer from poorer digital literacy (McLay & Reyes, 2019) and a sense of digital inequity for those who lack autonomy or feel overwhelmed by educational technology are the most salient challenges confronting teacher education programs in TALL environments.…”
Section: Discussionmentioning
confidence: 99%
“…A recurring theme unearthed in our collective biographies is that in enacting smart pedagogy we regularly encountered discomfort which in turn became useful as an integral “part of the teachers’ identity” (Daniela 2019 , p. 18). In our conversations, we agreed to be open “to develop new ways of being learners and teachers in relation to technology” (McLay and Reyes 2019a , p. 24). We now share two more narratives that highlight how identities emerged in the intersection of discomfort and smart pedagogy.…”
Section: Discussion and Analysis: Themes From Our Sensemaking Narrativesmentioning
confidence: 99%